Critical swimming speed and critical stroke rate in intermittent aerobic exercise - Clipet, B.; Dekerle, J.; Pelayo, P.; Sidney, M. (Biomechanics and Medicine in Swimming IX, 2003)
Critical swimming speed (CSScont) and critical stroke rate (CSRcont) in continuous exercises represent useful criteria to control intensity and technical training aerobic loads (Wakayoshi et al., 1992, Toussaint et al, 1997; Pelayo et al, 2000). Hence, the purpose of this study was to validate critical swimming speed (CSSint) and critical stroke rate (CSRint) concepts during intermittent swimming exercise. The main finding of this study showed that CSSint and CSRint could be used as useful criteria to control intensity and technical aspects in aerobic intermittent training. Moreover, intermittent exercise was dependent upon the same amount of energy required than in the continuous one and the difference noticed in SI and RPE values highlighted interest of aerobic intermittent training.